2020
DOI: 10.1109/access.2020.3006029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Community Detection Algorithm Based on Paring, Splitting and Aggregating in Internet of Things

Abstract: The explosive growth of Internet of Things (i.e., IoT) terminal equipment makes its topology more complex, which leads to the increasing cost of network research. Recently, the implicit community structure is widely used to improve the efficiency of research. However, most of the non-overlapping community detection algorithms have some weakness, such as the large number of community detected and the obvious scale gap between communities. To address these abovementioned problems, we design a novel non-overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Zarandi et al [17] arbitrarily deleted some edges in the network according to the similarity between edges, resulting in some subgraphs as the main communities, and then some subgraphs were merged to get optimal communities. In the pairing, splitting and aggregating algorithm (PSA) [18], the whole network is split into several similar node sets as an essential step to detect the final communities.…”
Section: Related Workmentioning
confidence: 99%
“…Zarandi et al [17] arbitrarily deleted some edges in the network according to the similarity between edges, resulting in some subgraphs as the main communities, and then some subgraphs were merged to get optimal communities. In the pairing, splitting and aggregating algorithm (PSA) [18], the whole network is split into several similar node sets as an essential step to detect the final communities.…”
Section: Related Workmentioning
confidence: 99%
“…Most studies reported that retain auditing protocols to avoid leakage of privacy [2], [21]- [28]. Simultaneously, lightweight methods [29]- [35] are being implemented to advance the IoT and Smart devices to meet the audit process's productivity needs.…”
Section: Related Workmentioning
confidence: 99%
“…Because the data stored in cloud for sharing can face many privacy challenge such as identity privacy and sharing data privacy. Scheme [21]- [29] proposed privacy preserving auditing protocols to prevent privacy leaking. At the same time, with the development of Internet of things and mobile devices, lightweight schemes [30]- [36] are proposed to satisfying the efficiency needs of auditing process.…”
Section: The Related Workmentioning
confidence: 99%